2005
DOI: 10.1172/jci21968
|View full text |Cite
|
Sign up to set email alerts
|

Oxidant stress from nitric oxide synthase–3 uncoupling stimulates cardiac pathologic remodeling from chronic pressure load

Abstract: Cardiac pressure load stimulates hypertrophy, often leading to chamber dilation and dysfunction. ROS contribute to this process. Here we show that uncoupling of nitric oxide synthase-3 (NOS3) plays a major role in pressure load-induced myocardial ROS and consequent chamber remodeling/hypertrophy. Chronic transverse aortic constriction (TAC; for 3 and 9 weeks) in control mice induced marked cardiac hypertrophy, dilation, and dysfunction. Mice lacking NOS3 displayed modest and concentric hypertrophy to TAC with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
316
4
9

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 406 publications
(343 citation statements)
references
References 71 publications
14
316
4
9
Order By: Relevance
“…When BH 4 availability is limiting, electron transport within the active site becomes "uncoupled" from L-arginine oxidation, causing a reduction of oxygen to superoxide (34). Depletion in BH 4 and eNOS uncoupling has been correlated with cardiac dysfunction in murine models of hypertension and transverse aortic constriction (35,36). Compared with WT mice, CSE KO mice had significantly lower cardiac BH 4 levels, and a trend toward higher dihydrobiopterin (BH 2 ) levels.…”
Section: Discussionmentioning
confidence: 99%
“…When BH 4 availability is limiting, electron transport within the active site becomes "uncoupled" from L-arginine oxidation, causing a reduction of oxygen to superoxide (34). Depletion in BH 4 and eNOS uncoupling has been correlated with cardiac dysfunction in murine models of hypertension and transverse aortic constriction (35,36). Compared with WT mice, CSE KO mice had significantly lower cardiac BH 4 levels, and a trend toward higher dihydrobiopterin (BH 2 ) levels.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac hypertrophy, fibrosis and gene expression changes are all consequences of POL, a commonly used animal model for cardiovascular research (Rockman et al 1991, De Windt et al 2001, Asakawa et al 2002, McMullen et al 2003, Liao et al 2004, De Acetis et al 2005, Takimoto et al 2005. However, their correlations with direct measurements of hemodynamic parameters in POL have not been determined in conscious ambulatory mice.…”
Section: Discussionmentioning
confidence: 99%
“…This model, including both transverse aortic constriction and abdominal aortic constriction, was adapted to mice and has been widely used in cardiovascular research (Rockman et al 1991, De Windt et al 2001, Asakawa et al 2002, McMullen et al 2003, Liao et al 2004, De Acetis et al 2005, Takimoto et al 2005. To produce the POL the aorta is commonly constricted by tying a suture against a needle to standardize the degree of restriction.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 This imbalance in NO/superoxide production results in oxidative stress, a major contributing factor in a variety of vascular diseases, 7,9,10 which also leads to detrimental effects on cardiac function. 11 Previous studies in our group and others have shown that BH 4 plays a pivotal role in regulating NO/superoxide balance in the pulmonary vasculature. [12][13][14] It has been shown that hph-1 mice, deficient in GTP-cyclohydrolase 1 (GTPCH-1), the rate limiting enzyme for BH 4 production, show pulmonary vascular remodeling and right ventricular hypertrophy under normoxic conditions, accompanied by significantly increased superoxide production in the lung.…”
Section: Introductionmentioning
confidence: 90%